Anthropocene Epoch: Rethinking the Environmental and Political Philosophy in the Global Environmental Crisis - Richard Sťahel (Filozofia)
Introduction to the monothematic block "Anthropocene Epoch: Rethinking the Environmental and Political Philosophy in the Global Environmental Crisis."